Correlation between Perturbation of Redox Homeostasis and Antibiofilm Capacity of Phytochemicals at Non-Lethal Concentrations - Michael S. Christodoulou; Federica Villa; Andrea Pinto; Francesca Cappitelli (Antioxidants, 2022)
Biofilms are the multicellular lifestyle of microorganisms and are present on potentially every type of biotic or abiotic surface. Detrimental biofilms are generally targeted with antimicrobial compounds. Phytochemicals at sub-lethal concentrations seem to be an exciting alternative strategy to control biofilms, as they are less likely to impose selective pressure leading to resistance. This overview gathers the literature on individual phytocompounds rather than on extracts of which the use is difficult to reproduce. To the best of our knowledge, this is the first review to target only individual phytochemicals below inhibitory concentrations against biofilm formation. We explored whether there is an overall mechanism that can explain the effects of individual phytochemicals at sub-lethal concentrations. Interestingly, in all experiments reported here in which oxidative stress was investigated, a modest increase in intracellular reactive oxygen species was reported in treated cells compared to untreated specimens. At sub-lethal concentrations, polyphenolic substances likely act as pro-oxidants by disturbing the healthy redox cycle and causing an accumulation of reactive oxygen species.